The intestinal microbiota predisposes to traveler's diarrhea and to the carriage of multidrug-resistant Enterobacteriaceae after traveling to tropical regions. (3rd September 2019) - Leo, Stefano; Lazarevic, Vladimir; Gaïa, Nadia; Estellat, Candice; Girard, Myriam; Matheron, Sophie; Armand-Lefèvre, Laurence; Andremont, Antoine; Schrenzel, Jacques; Ruppé, Etienne
ABSTRACT: The risk of acquisition of multidrug-resistant Enterobacteriaceae (MRE) and of occurrence of diarrhea is high when traveling to tropical regions. The relationships between these phenomena and the composition of human gut microbiota have not yet been assessed. Here, we investigated the dynamics of changes of metabolically active microbiota by sequencing total RNA from fecal samples taken before and after travel to tropical regions. We included 43 subjects who could provide fecal samples before and after a travel to tropical regions. When found positive by culturing for any MRE after travel, the subjects sent an additional sample 1 month later. In all, 104 fecal samples were considered (43 before travel, 43 at return, 18 one month after travel). We extracted the whole RNA, performed retrotranscription and sequenced the cDNA (MiSeq 2x300bp). The reads were mapped to the reference operational taxonomic units (OTUs) and species/strains using the 16S Greengenes and 23S SILVA databases. We found that the occurrence of diarrhea during the travel was associated with a higher relative abundance of Prevotella copri before departure and after return. The composition of microbiota, before travel as well as at return, was not correlated with the acquisition of MRE. However, the clearance of MRE one month after return was linked to a specific pattern of bacterial species that was also found before and after return. In conclusion, we found specific OTUs associated to a higher risk of diarrhea during a stay in tropical regions and to a faster clearance of MRE after their acquisition.